An analysis of additional energy requirement to meet the sustainable development goals. (1st November 2020) - Simsek, Yeliz; Santika, Wayan G.; Anisuzzaman, M.; Urmee, Tania; Bahri, Parisa A.; Escobar, Rodrigo
Abstract: United Nations' members came together in 2015 and agreed on seventeen sustainable development goals which include hundred and sixty-nine targets related to sustainable development into the overall economic, environmental and social contexts of countries to be achieved by 2030. In order to achieve these goals, more effort may be required than the current policies and strategies. This is particularly true for the energy sector as energy is the key enabler for all development activities. Therefore, there is a need to analyse the required effort and energy to implement these goals based on countries' specific context. The objective of this paper is to assess the indicators of energy-related sustainable development goals and calculate the additional energy requirement to achieve each goal by 2030 for Chile. The key findings of the research indicate that Chile will meet fourteen energy-related sustainable development targets by 2030 under the business as usual scenario. However, Target 2.1, Target 5.b, Target 12.3, Target 13.1, and Target 17.6 require extra energy to meet sustainable development goals in Chile by 2030. Approximately 16 million GJ additional energy is required in order to meet energy-related sustainable development goals in Chile than the business as usual scenario by 2030. This research output can provide insights to researchers trying to assess the achievement of sustainable development goals in other developing countries.